Unintentional false lumen placement of frozen elephant trunk in aortic dissections: root cause analysis of morphological risk factors - Körfer, Daniel; Wong, Brian; Fujii, Masahiko; Hori, Daijiro; Takagi, Daichi; Wortmann, Markus; Geisbüsch, Philipp; Manesh, Michelle; Magee, Gregory A; Karck, Matthias; Meisenbacher, Katrin; Böckler, Dittmar; et al. (European journal of cardio-thoracic surgery, 2025)
To analyse morphological features associated with unintentional frozen elephant trunk (FET) placement in the false lumen (FL) during aortic dissection (AD) repair.This multicentre retrospective study enrolled patients with acute/chronic AD with unintentional FET placement in the FL. To identify morphological features, pre-/postoperative CT, clinical and procedural data were assessed. Imaging analysis focused on size and position of the relevant (re-)entry (rE) in the distal aortic arch and postoperative FET-position.Thirteen male patients (54 years, interquartile range [IQR]: 18 years) from 6 international centres were included between 2017 and 2023. Aortic pathologies comprised 5 acute Type-A-AD (38.5%), 4 acute Type-B-AD (30.8%), 1 chronic Type-B-AD (7.7%), and 3 chronic expanding residual Type-A-AD (23.1%). The rE (first [re-]entry distal to left subclavian artery [LSA] origin) had a median diameter of 15.5 mm (IQR: 9.4 mm) and was mostly located in zone 3 (61.5%), the outer curvature (61.5%), and 21.1 mm (IQR: 26.4 mm) distal to the LSA. The stented portion of the FET (FETSP) lengths measured 60-190 mm. FETSP proximal end was mostly located in zone 1 (38.5%) and at median distance of 28.2 mm (IQR: 26.5 mm) from the native LSA. FETSP distal end was mostly located in zone 5 (61.5%). Median calculated distance from rE to FETSP proximal end was 38.9 mm (IQR: 39.0 mm). Three patients (23.1%) died perioperatively; the others remained asymptomatic (follow-up: 13 mo [IQR: 15 mo]).Large (re-)entries in the outer curvature of the distal aortic arch are common in patients with FET placement in the FL. Interdisciplinary collaboration with controlled, wire-guided FET placement and usage of advanced intraoperative imaging (cone-beam-CT, transesophageal echocardiography, intravascular ultrasound, angioscopy) may help minimize risk of FL deployment.
Veröffentlicht: 11. Oktober 2025
Gesehen am 05.12.2025